Analisis Kemampuan Kognitif Siswa dan Hasil Belajar Fisika Kelas XI SMA Islam Al-Falah Jambi - Yanti, Nurhikma; Putri, Amanda; Febriana, Nadilla (Journal of Pedagogi, 2024)
This study aims to analyze cognitive abilities and physics learning outcomes at Al-Falah Islamic High School in Jambi City. The method used is quantitative method. The type of research used is This type of research is field research, namely research conducted by going directly to the field to examine cognitive abilities and comparison of learning outcomes. The subjects and samples in this study were students of class XI IPA 2 at Al Falah Islamic High School, Jambi City, totaling 30 students. The research instrument used in this study was a test question with 50 questions. The sampling technique used in this study was purposive sampling technique. The data analysis used in this study was miles and huberman with research procedures, namely analyzing literature, determining instruments, collecting data, analyzing data, and concluding the results of research data. The results of this study indicate that cognitive abilities at Al-Falah Islamic High School in Jambi City on newton's law material still need to be improved. The results of the independent sample T test analysis show that sig. (2-tailed) 0.530> 0.05. This means that there is no significant difference between learning outcomes in male and female students. This is because cognitive abilities play an important role in helping students to know learning knowledge and physics learning outcomes on newton's law material.